Building care gerontotechnologies in the context of elderly person with Alzheimer's disease - Francine Casarin; Francisco Fernandes; Rosiane Filipin Rangel; Daiane Porto Gautério-Abreu; Oclaris Lopes Munhoz; Silomar Ilha (Rev Rene)
Objective: to build care gerontotechnologies to help family caregivers with the difficulties experienced in the context of elderly people with Alzheimer's disease. Methods: strategic action research carried out with seven family caregivers of elderly people with Alzheimer's disease and 12 health academics from a university. Data was gathered from the family caregivers using a semi-structured interview. Three focus groups were held with the academics. The data was submitted to the discursive textual analysis technique. Results: eight difficulties experienced by family caregivers emerged, corresponding to cognitive aspects, Activities of Daily Living and issues relating to family care. It was possible to construct 14 care gerontotechnologies in product form. Conclusion: gerontotechnologies were built to help family caregivers with the difficulties experienced by elderly people living with Alzheimer's disease. Contributions to practice: the gerontotechnologies developed have the potential to contribute to the care process, since they can be used by family caregivers on a daily basic and can be adapted to each reality, based on the unique needs of each elderly person.